Supplementary Calcium Restores Peanut (Arachis hypogaea) Growth and Photosynthetic Capacity Under Low Nocturnal Temperature - Song, Qiaobo; Liu, Yifei; Pang, Jiayin; Yong, Jean Wan Hong; Chen, Yinglong; Bai, Chunming; Gille, Clément; Shi, Qingwen; Wu, Di; Han, Xiaori; Li, Tianlai; Siddique, Kadambot H. M.; et al. (Frontiers in Plant Science, 2020)
Peanut (Arachis hypogaea L.) is a globally important oil crop, which often experiences poor growth and seedling necrosis under low nocturnal temperatures (LNT). This study assessed the effects of supplementary calcium (Ca2+) and a calmodulin inhibitor on peanut growth and photosynthetic characteristics of plants exposed to LNT, followed by recovery at a higher temperature. We monitored key growth and photosynthetic parameters in a climate-controlled chamber in pots containing soil. LNT reduced peanut growth and dry matter accumulation, enhanced leaf nonstructural carbohydrates concentrations and non-photochemical quenching, decreased the electron transport rate, increased the transmembrane proton gradient, and decreased gas exchange rates. In peanut subjected to LNT, foliar application of Ca2+ restored growth, dry matter production and leaf photosynthetic capacity. In particular, the foliar Ca2+ application restored temperature-dependent photosynthesis feedback inhibition due to improved growth/sink demand. Foliar sprays of a calmodulin inhibitor further deteriorated the effects of LNT which validated the protective role of Ca2+ in LNT tolerance of peanut.